Comparative analysis of the financial performance of Bank Riau Kepri Syariah before and after conversion - Busyro, Wahyi; Abdullah, Azwan bin; Din, Noormariana binti Mohd (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study compares the financial performance of Bank Riau Kepri Syariah before and after its conversion into a fully Islamic bank, focusing on the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Return on Assets (ROA). Using quantitative data from 16 quarterly periods, the results reveal no significant changes in CAR and NPF, but a significant decline in ROA, indicating a decrease in short-term profitability following the conversion.Design/Methodology/Approach: The study employs a quantitative approach by analyzing financial data from 16 quarters (10 before and 6 after the conversion) using SPSS for statistical testing.Research findings: The results show no significant difference in CAR between the pre-conversion (21.733%) and post-conversion (21.69%) periods. Similarly, there is no significant difference between the pre-conversion NPF (2.697%) and the post-conversion NPF (2.39%). However, a significant difference is found in ROA, which declined from 2.611% to 1.55% after conversion, indicating a notable decrease in profitability.Theoretical contribution/Originality: This study contributes to institutional theory by illustrating how regulatory and organizational changes in Islamic banking affect financial performance through coercive, normative, and mimetic pressures.Practitioner/Policy implication: The findings offer valuable insights for regulators, managers, and policymakers in assessing the short-term financial risks of a full conversion to Islamic banking, emphasizing the importance of strategic planning, human resource preparedness, and regulatory compliance during transformation.Research limitation/Implication: This study focuses on a single case—the full conversion of Bank Riau Kepri Syariah—using real-time quarterly data to compare CAR, NPF, and ROA ratios since 2022. As one of Indonesia’s first regionally owned banks to complete a full transformation into an Islamic bank, Bank Riau Kepri provides a unique context for evaluating the financial impact of conversion.